English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

These are two seperate equations.

-3x^0(2x - 3) - (-2^0) - 2 = 5(X - 3^0)2

and

-3 -3^0 -3^2(2x - 5) -(-2x - 3) = -x^0(x - 3)

both should come out to fractions, if I am correct. I get a little mixed up when i have numbers to the zero power. For the first one I got 8/9ths, and for the second, 41/15. I may have fluked on a step or two..

2006-10-04 03:15:07 · 2 answers · asked by Ryan 1 in Science & Mathematics Mathematics

2 answers

3x^0(2x - 3) - (-2^0) - 2 = 5(X - 3^0)2
3(2x-3)+1-2=5x^2
6x-9-1=5x^2
5x^2-6x+10=0
using the quadratic equation:
x= (6+-sqrt(36-4(5)(10)))/2(5)
which does not have any real solutions since
36-4(5)(10)<0

-3 -3^0 -3^2(2x - 5) -(-2x - 3) = -x^0(x - 3)
-3-1-9(2x-5)+2x+3=-x+3
-4-18x+45+2x+3= -x+3
-18x+2x+x=4-45
-15x=-41
x=41/15

2006-10-04 03:45:28 · answer #1 · answered by Anonymous · 1 0

first of all, anything to the zero power is 1 (except zero itself!).

So your first equation works out to:
-3(1)(2x-3) - (1) - 2 = 5(x-1)2

now just simplify...
-6x+9-1-2 = 10x-10
16 = 16x
x = 1

I'll let you do the second one on your own. Post your answer and I'll tell you if you're right.

2006-10-04 10:22:15 · answer #2 · answered by i_sivan 2 · 0 1

fedest.com, questions and answers